Effect of Ascophyllum nodosum extracts on the growth, yield and antioxidant capacity of Haematococcus pluvialis carotenoids - Guajardo-Barbosa, Claudio; Galán-Wong, Luis Jesús; Beltrán-Rocha, Julio César; Quintero-Zapata, Isela; Gandarilla-Pacheco, Fátima Lizeth; Pereyra-Alferéz, Benito; Santos, Myriam-Elías; Luna-Olvera, Hugo Alberto (Revista de Biología Marina y Oceanografía, 2020)
Recent research has shown that the use of biological extracts, which contain a wide variety of nutrients and phytohormones are potentially useful in the production of plants of agricultural importance. Seaweed extracts are particularly rich in minerals and micronutrients necessary for the growth of microalgae. The effect of three commercial extracts of Ascophyllum nodosum as plant growth inducers (Stimplex®, Acadian Soils® and Liquid Seaweed Concentrate®), provided by Acadian Sea Plants Ltd., were evaluated in relation to the growth and production of biomass and carotenoids in Haematococcus pluvialis. The results were evaluated by one-way ANOVA and post-hoc analysis utilizing Tukey’s test with a significance level of 95% (α= 0.05). The reference medium used was the Bold basal medium, to which 250 ppm of each extract was added. The Stimplex® extract had an increase of 22.79% in cell density and 17% in dry matter, higher than the control culture. The content of carotenoids and antioxidant capacity, respectively, with Stimplex® was 30.05% and 141.76% higher than the control culture.